PENINGGALAN SEJARAH SEBAGAI SUMBER BELAJAR SEJARAH DALAM PENANAMAN NILAI-NILA KEBANGSAAN DI KECAMATAN MUNCAR KABUPATEN BANYUWANGI - Agus Mursidi; Dhalia Sutopo (Khazanah Pendidikan, 2019)
Historical relics in both the Royal Age and Colonialism Period, it is necessary to identify and document historical heritage. This becomes important so that it becomes the basis of concern for both the community itself and also from the Regional Government so that it can be used as input in the cultural heritage inventory. This research is to identify historical relics in Muncar sub-district in order to inventory and the results of the study are used as a foothold for stakeholders especially the cultural preservation and historical relics. This study uses a qualitative approach with a case study design that uses a phenomenological perspective. The selection of respondents used snow ball, in which the sample in this study was the village and sub-district governments as well as cultural and historians in the muncar sub-district. With the results of the study showed that 1. Lack of public awareness to maintain historical heritage sites, 2. Still the role of government is needed to protect and preserve it through education and tourism, 3. Changes in several forms so as to reduce the value and authenticity of the site itself.            Keywords: Historical heritage, Learning Resources, Nationality